Investigation of Loneliness Perception of High School Students according to Participating in Recreational Activities and Individual Variables - EKİNCİ, Nurullah Emir; DEMİREL, Mehmet; HARMANDAR DEMİREL, Duygu; IŞIK, Utku (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2015)
This paper aimed to investigate loneliness perception of high school students in terms of participating in recreational activities and various variables such as gender, number of friends & number of brothers/sisters, living environment, kind leisure activity and place of participating in these activities. The study sample consisted of 392 high school students and they were selected randomly. “UCLA Loneliness Scale” was used as data gathering tool. Analysis of the data obtained was carried out by using “SPSS for Windows” software package program. In addition to descriptive statistics, “Mann Whitney U” and “Kruskal Wallis” were performed in order to determine whether loneliness perception of the participants’ differs according to some personal characteristics. As a result, there was no significant difference between loneliness perception of participants’ according to gender, number of brothers/sisters and living environment. But according to participant’s number of friends, leisure activity and place of participating in these activities significant differences were found between participants’ loneliness perception.